Influence of hip joint`s flexibility on appearance of spine injuries in gymnastics - Sumer, T.; Pajek, M.; Hadzic, V.; Samardzija Pavletic, M. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
The purpose and goals of this final degree thesis were to investigate the appearance of spine injuries (lumbar spine) in Slovenian gymnasts as well as to assess whether the flexibility of the hip joint - in directions of flexion and extension - affects these injuries. Another goal was to assess whether the hip joint flexibility differs from the normal values of the general population, as well as find the differences in the range of flexion and extension of the hip joint in between different types of gymnastics. Our research is one of the primary steps in determining normal values in the range of flexion and extension in hip joint. This was the key reason why we decided to complete the research. The research population consisted of 55 individuals - 18 of those participating in men`s artistic gymnastics (MAG), 10 in women`s artistic gymnastics (WAG), and 27 in rhytmic gymnastics (RG). The first part of this thesis is based on a one-year observation of these individuals and analysis of their personal data, as well as practice and injury information. The second part of the project revolves around measurement of passive hip joint flexibility. The measurements were taken using goniometry. 33% of participants got injured during the one year of observation. The group with the highest percentage of injuries is women`s artistic gymnastics (40%), followed by men`s artistic gymnastics (28%). All participants` measured values of hip joint flexion exceeded the normal values. However, the normal values for ejection were met only by the participants belonging to the rhythmic gymnastics group. Statistically significant differences between flexibility of the left and right side of the hip joint appeared between men`s and women`s artistic gymnastics group during the flexion on the left side. Another set of statistically significant differences appeared between men`s artistic gymnastics group and rhytmic gymnastics on the hip during the flexion and extension on the right and during the flexion on the left side. Statistically significant difference between the range of flexion and extension on the left and the right side of the hip joint (symmetry) only appeared during the flexion of rhythmic gymnastics group - there were no significant differences with other groups. The injured population have greater range of flexion on both sides of the hip joint. On the contrary, healthy (uninjured) population had greater range of extension on both sides of the hip joint. Nonetheless, there were no statistically significant differences between injures and healthy population in terms of both flexion and extension on both sides of the hip joint. Statistically significant differences only appeared during the left hip flexion of the healthy population between men`s artistic gymnastics and women`s artistic gymnastics, as well as during the right hip flexion of healthy population between men`s artistic gymnastics and rhytmic gymnastics. Results can be the starting point for planning and carrying out preventive training, in the direction of instability of the hip joint due to excessive flexibility or in the direction of an increased risk of injury due to insufficient flexibility.